Estudo da comunidade de microrganismos redutores de sulfato (BRS) provenientes do sedimento do reservatório de Retiro Baixo/Pompéu e sua capacidade de resistência a metais, após o rompimento da barragem de rejeitos I de Brumadinho - Montanari, Anna Flavia Pereira (2023)
The main objective of this study was to evaluate the behavior of sulfate-reducing bacteria present in the sediment of the Retiro Baixo reservoir, located between the municipalities of Curvelo and Pompéu, Minas Gerais, after the rupture of Dam I of the Córrego do Feijão mine, in the municipality from Brumadinho, MG. Samples were collected 5 days after the rupture, and eight other periodic collections during the years 2019, 2020, 2021 and 2022. For the quantitative analyses, assays were performed to quantify the BRS through multiple tubes and the values determined by the MPN. The quantification result showed a significant increase of 6 orders of magnitude in the cell count per 100ml between campaigns 06 and 07. In campaign 08 the concentration of BRS remained in the same order of magnitude and in campaign 09 there was a 100-fold reduction in the number of cells per 100 ml of sample. Resistance tests of these microorganisms to iron and manganese were carried out for campaigns numbered 01, 02, 06 and 08, which correspond to periods of 5 days after the rupture, 3 months, 30 months and 36 months, respectively. The ability to remove sulfate and metal dissolved in the liquid medium for different concentrations over the chosen campaigns were observed. For iron, the concentrations used were 100, 200, 300 and 400 mg/L, which showed a reduction in sulfate in all treatment flasks, only with a lower efficiency in the concentration of 400 mg/L in campaign 01, demonstrating that there was an increase in the microbial resistance of the sediment between the first two campaigns and the removal of dissolved metals showed that dissolved iron was almost completely removed in all tests. For manganese, concentrations of 20, 340, 60 and 80 mg/L were used, and sulfate removal remained high at all concentrations and throughout the analyzed campaigns, and the Mn removal rate was above 80%.